Developmental effects of constitutive mTORC1 hyperactivity and environmental enrichment on structural synaptic plasticity and behaviour in a rat model of autism spectrum disorder - Granak, Simon; Tuckova, Klara; Kutna, Viera; Vojtechova, Iveta; Bajkova, Laura; Petrasek, Tomas; Ovsepian, Saak V (The European journal of neuroscience, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental condition causing a range of social and communication impairments. Although the role of multiple genes and environmental factors has been reported, the effects of the interplay between genes and environment on the onset and progression of the disease remains elusive. We housed wild-type (Tsc2+/+) and tuberous sclerosis 2 deficient (Tsc2+/-) Eker rats (ASD model) in individually ventilated cages or enriched conditions and conducted a series of behavioural tests followed by the histochemical analysis of dendritic spines and plasticity in three age groups (days 45, 90 and 365). The elevated plus-maze test revealed a reduction of anxiety by enrichment, whereas the mobility of young and adult Eker rats in the open field was lower compared to the wild type. In the social interaction test, an enriched environment reduced social contact in the youngest group and increased anogenital exploration in 90- and 365-day-old rats. Self-grooming was increased by environmental enrichment in young and adult rats and decreased in aged Eker rats. Dendritic spine counts revealed an increased spine density in the cingulate gyrus in adult Ekers irrespective of housing conditions, whereas spine density in hippocampal pyramidal neurons was comparable across all genotypes and groups. Morphometric analysis of dendritic spines revealed age-related changes in spine morphology and density, which were responsive to animal genotype and environment. Taken together, our findings suggest that under TSC2 haploinsufficiency and mTORC1 hyperactivity, the expression of behavioural signs and neuroplasticity in Eker rats can be differentially influenced by the developmental stage and environment.
Keywords: Mechanistic Target of Rapamycin Complex 1; poruchy autistického spektra; Rats; neuroplasticita; dendritic spine; Eker rats; Neuronal Plasticity; Autism Spectrum Disorder; animal models of autism; pyramidové buňky; hipokampus; tuberous sclerosis complex; Disease Models, Animal; cingulate gyrus; open field test; Pyramidal Cells; krysa rodu Rattus; enriched environment; modely nemocí na zvířatech; zvířata; mTORC1; Hippocampus; Animals